Prognostic Value of COX-2, NF-κB, and Sp1 Tissue Expressions in Pancreatic Ductal Adenocarcinoma: A Systematic Review and Meta-analysis - Kaka Renaldi; Marcellus Simadibrata; Nur Rahadiani; Diah Rini Handjari; Andy William; Fira Sinuraya; Dadang Makmun (Turkish Journal of Gastroenterology, 2021)
Background: Pancreatic ductal adenocarcinoma (PDAC) is deadly cancer with a poor prognosis. Molecular prognostic markers are needed to predict the patient’s survival. The cyclooxygenase-2 enzyme (COX-2) and its 2 major transcription factors––nuclear factorkappa B (NF-κB) and specificity protein 1 (Sp1)––are activated during inflammation caused by neoplasia. Several studies have investigated the association between the COX-2, NF-κB, and Sp1 tissue expressions with the patient’s overall survival. Therefore, we conducted this systematic review and meta-analysis to evaluate those studies. Methods: We searched for relevant articles from the MEDLINE database through June 2020. Studies were eligible if they included dichotomized tissue protein expression status and the overall survival as the outcome. We used RevMan and ProMeta programs to perform the meta-analysis. Results: We identified 11 eligible studies. The meta-analysis showed that COX-2 tissue expression was associated with decreased overall survival (crude HR = 1.35; 95% CI, 1.05-1.74), although the result was not significant when controlling for other covariates. The NF-κB tissue expression was associated with decreased overall survival (crude HR = 2.18; 95% CI, 1.49-3.18), although it was not significant when controlling for other covariates. The Sp1 tissue expression showed significantly decreased overall survival even when adjusted with other covariates (aHR = 3.47; 95% CI, 1.52-7.94). The limitations included searching only for English publications and the substantial heterogeneity among the studies. Conclusion: COX-2, NF-κB, and Sp1 tissue expressions have the potential to be used as prognostic markers in PDAC. Further studies are still needed to clarify the associations. Cite this article as: Renaldi K, Simadibrata M, Rahadiani N, et al. Prognostic value of COX-2, NF-κB, and Sp1 tissue expressions in pancreatic ductal adenocarcinoma: A systematic review and meta-analysis. Turk J Gastroenterol. 2021;32(11):956-970.